TINJAUAN COST-EFFECTIVENESS ANALYSIS PENGGUNAAN INSULIN SECARA ASEPTIC DISPENSING DI RAWAT INAP RSUD TEBET: TINJAUAN COST-EFFECTIVENESS ANALYSIS PENGGUNAAN INSULIN SECARA ASEPTIC DISPENSING DI RAWAT INAP RSUD TEBET - Muzakar, Cholid (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2024)
Diabetes mellitus is a chronic disease that requires continuous medical care. Diabetes mellitus is defined as a disease or chronic metabolic disorder with multiple etiologies. It is characterized by high blood sugar levels accompanied by impaired carbohydrate, lipid, and protein metabolisms as a result of insulin insufficiency. The prevalence of people with diabetes mellitus increases constantly every year. Insulin is one of the therapeutic options formed by PERKENI and PAPDI to treat hyperglycemic patients, both outpatients and inpatients. The purpose of this study is to find the cost-efficiency by sharing the insulin dispensed following rules of aseptic dispensing for inpatients at Tebet General Hospital. The method of the study was an observational study with a descriptive design. Data were obtained from the pharmacy installation of sterile medication mixing forms for inpatients who used shared insulin from January to September 2023. 81% of 121 hospitalized patients who were diagnosed with diabetes mellitus used insulin as the therapy. The cost-effectiveness review stated that the use of shared insulin which was dispensed aseptically could save insulin dispensing costs with an average savings 33% or Rp.1,435,943,- per month. It concludes that the use of shared insulin which is dispensed aseptically for inpatient care can save patient care costs and insulin dispensing costs at the pharmacy installation of the hospital. Keywords: cost-efficiency, Diabetes Mellitus, inpatient, shared insulin, aseptic dispensing,